TUNTUTAN DAN TANTANGAN PENDIDIK DALAM TEKNOLOGI DI DUNIA PENDIDIKAN DI ERA 21 - Suprapto Gunawan; Sri Widiati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The demands and challenges of educators in technology in the world of education in the 21st era are now the use of technology in the world of education where educators are required to